2008
DOI: 10.1097/fjc.0b013e31817e0edd
|View full text |Cite
|
Sign up to set email alerts
|

Differential Long-term Effects of Carvedilol on Proinflammatory and Antiinflammatory Cytokines, Asymmetric Dimethylarginine, and Left Ventricular Function in Patients With Heart Failure

Abstract: Neuroendocrine/inflammatory and endothelial functions have been indicated as crucial for heart failure (HF) patients. We evaluated relation in HF patients among cytokines and asymmetric dimethylarginine (ADMA) and left ventricular ejection fraction (LVEF) at baseline and after long-term administration of carvedilol. Interleukin 10 (IL-10), interleukin 18 (IL-18), and ADMA were measured in 22 NYHA class II to IV HF patients at baseline and after 40 +/- 14 months of carvedilol treatment. Patients were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Similarly, some but not all antihypertensive drugs have been shown to be associated with a reduction in ADMA concentration and the effects seemed not to be a class effect [12][13][14]. Therefore, further studies are needed to assess which drugs may have an effect on ADMA concentration and whether a reduction will have long-term consequences on risk of cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some but not all antihypertensive drugs have been shown to be associated with a reduction in ADMA concentration and the effects seemed not to be a class effect [12][13][14]. Therefore, further studies are needed to assess which drugs may have an effect on ADMA concentration and whether a reduction will have long-term consequences on risk of cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed ␤-adrenergic blockade by celiprolol prevents LVH induced by aortic banding, but such a beneficial effect of ␤-blockade is almost completely abolished by NO inhibition (36). Carvedilol, a ␤-adrenergic blocker with anti-oxidant properties, increases survival and decreases plasma ADMA in patients with heart failure (37) and reduces mortality in stage 5D-CKD patients with cardiomyopathy (38).…”
Section: Discussionmentioning
confidence: 99%
“…The cytokines hypothesis for HF holds that HF progresses, at least in part, as a result of the toxic effects exerted by endogenous cytokine cascades on the heart and the peripheral circulation [51,52]. Interleukin (IL)-18 is among the pro-inflammatory cytokines involved in cardiovascular changes [53] and serum IL-18/IL-10 ratio is an independent predictor of adverse cardiovascular events in acute coronary syndrome patients [54,55].…”
Section: Carvedilol Other Than Its Traditional Propertiesmentioning
confidence: 99%
“…Interleukin (IL)-18 is among the pro-inflammatory cytokines involved in cardiovascular changes [53] and serum IL-18/IL-10 ratio is an independent predictor of adverse cardiovascular events in acute coronary syndrome patients [54,55]. Alfieri et al have reported that long-term treatment with carvedilol induced an improvement in symptoms of HF paralleled by an increase of IL-10 levels and a reduction of IL-18 levels, resulting in a 9-times reduction of IL-18/IL-10 ratio and reaching values similar to healthy subjects [52]. However, in this subpopulation of HF patients, inflammation, endothelial function and LV response to carvedilol do not appear to be strictly related [52].…”
Section: Carvedilol Other Than Its Traditional Propertiesmentioning
confidence: 99%
See 1 more Smart Citation